2010
DOI: 10.1097/wnr.0b013e32833fcba4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vasoactive intestinal polypeptide release in the suprachiasmatic nucleus circadian clock

Abstract: Timing of the mammalian circadian clock of the suprachiasmatic nucleus (SCN) is regulated by photic input from the retina. Retinorecipient units entrain rhythmicity of SCN pacemaker cells in part through their release of vasoactive intestinal polypeptide (VIP). The underlying nature of this process is conjectural however, as in vivo SCN VIP release has never been measured. Here, SCN microdialysis was used to investigate mechanisms regulating VIP. Hamsters under LD 14:10 exhibited a daily peak in synaptic VIP r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Daily oscillations in the expression of the transcript encoding VIP, as well as in VIP protein expression and VIP release in the SCN, have been reported (Okamoto et al, 1991; Shinohara et al, 1993; Francl et al, 2010). Indeed, it has been shown that the peak expression of both VIP mRNA and protein occurs during the subjective night (Okamoto et al, 1991; Shinohara et al, 1993; Ban et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daily oscillations in the expression of the transcript encoding VIP, as well as in VIP protein expression and VIP release in the SCN, have been reported (Okamoto et al, 1991; Shinohara et al, 1993; Francl et al, 2010). Indeed, it has been shown that the peak expression of both VIP mRNA and protein occurs during the subjective night (Okamoto et al, 1991; Shinohara et al, 1993; Ban et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that the peak expression of both VIP mRNA and protein occurs during the subjective night (Okamoto et al, 1991; Shinohara et al, 1993; Ban et al, 1997). VIP release, however, increases during the day (Francl et al, 2010), likely reflecting the daytime increase in the repetitive firing in VIP neurons. Interestingly, bath application of VIP alters the membrane and firing properties of SCN neurons for hours (Kudo et al, 2013), which may result in continued VIP release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of desynchronization is dose dependent in that VIP synchronizes at lower concentrations (21) and desynchronizes at higher concentrations. Although absolute concentrations of VIP in the SCN are unknown, VIP release is circadian and at low levels in the SCN based on in vitro and in vivo measures and, in vivo, increases as a function of light intensity (6,(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, VIP is involved in photic signaling (An, et al 2013; Colwell et al 2003; Dragich, et al 2010; Hughes, et al 2004; Kuhlman et al 2003; Lucassen, et al 2012; Shen, et al 2000), and light influences VIP expression in the SCN (Duncan et al 1995; Francl, et al 2010; Isobe and Nishino 1998; Shinohara and Inouye 1995; Smith and Canal 2009). Deficits in VIP signaling cause abnormal responses to light, with one result being an unusual responsiveness to light during the day.…”
Section: Scn Coupling Mechanismsmentioning
confidence: 99%